Concentrating solar thermal heat storage using metal hydrides - Harries, D.; Paskevicius, Mark; Sheppard, Drew; Price, T.; Buckley, Craig (IEEE, 2012)
Increased reliance on solar energy conversion technologies will necessarily constitute a major plank of any forward global energy supply strategy. It is possible that solar photovoltaic (PV) technology and concentrating solar thermal (CST) power technology will play roughly equal, but complementary roles by 2050. The ability to increase reliance on CST power technology during this period, however, will be constrained by a number of factors: the large plant sizes dictated by economies of scale, the high associated transmission infrastructure investment cost, and the limitations of current thermal energy storage technologies. Thus, solar technology's main midterm role is seen to be as hybrid solar thermal power plant. The development of low-cost, high-temperature, high-energy density thermal energy storage systems is needed to enable CST plants to be dispatchable and accelerate the deployment of this technology. Thermochemical storage has the best potential to achieve these energy storage requirements and a brief overview of thermochemical energy storage options for CST plants points to high-temperature metal-hydride thermochemical heat energy storage systems. Hydrogen storage systems offer the highest energy storage capacity per volume and are therefore the most likely candidates for achieving the goal of fully dispatchable CST plants. A number of high-temperature metal-hydride thermochemical solar energy storage systems have been proposed and a small number of these systems are currently being investigated and developed.A key component of this work is matching the thermochemical metal-hydride system with a suitable “low-temperature” hydrogen storage material to produce systems that are self-regulating. A summary of the development status of these systems suggests that, despite the technical challenges associated with high-temperature thermochemical energy storage systems, their potential advantages are now seeing development occurring. Although in the early stages, their commercialisation could be fast tracked.